Use of free and open-source software to identify structural lineaments and enhancement of geological structures - Puma Enriquez, Yessenia (2021)
This main objective of this study is the use of free and open source software to identify structural lineaments and enhancement of geological structures, without the need to use commercial software. In this study, a digital elevation model (DEM) with a resolution of 12.5 m ALOS PALSAR was used on which the different relief visualization techniques were performed, obtaining structural guidelines and enhancement of geological structures (possible faults), in addition graphs were made of rosettes and histograms, with the help of free and open source software such as SAGA GIS, QGIS 3.4.12, Stereonet and OpenStereo. The lineaments were analyzed by azimuth frequency, using different methods; Multidirectional shading, Shading with light variation every 30°, Combined shadows, Red Relief Image Map (RRIM); and finally the obtaining and processing of structural guidelines was carried out with each visualization technique, 745 were obtained with the multidirectional shading technique, 1173 by shading with light variation every 30°, 736 and 749 by the combined shadows 1 and 2 respectively and 139 geological structures representing faults inferred with the Red Relief Image Map (RRIM) technique; which indicate a trend in an Andean NW-SE direction. To complement the interpretation, rosette graphs and histograms were generated for each type of method, which when comparing them, 6 general trends were found; it is observed that the tendencies obtained in the different processes present similarity with the direction of the regional faults present in the study area. It is concluded that the techniques used are reliable, useful and complementary to each other to recognize, analyze, determine and interpret structural guidelines in a pre-field stage with the help of free and open source software.